JARINGAN KOMUNIKASI KELOMPOK BERBASIS MOBILE PHONE PEKERJA MIGRAN INDONESIA DI HONG KONG - Amin Shabana; Nani Nurani Muksin; Moh. Amin Tohari (Prosiding Seminar Nasional Unimus, 2020)
Mobile communication plays a strategic role for Indonesian migrant workers or PMI in Hong Kong. Theuse of this smartphone has a variety of purposes with different message content to the target audience.The purpose of this study is as follows: 1) PMI device-based communication in Hong Kong; 2) PMIGroup Communication Network in Hong Kong; this research uses a qualitative approach with descriptivemethods. The research center is located in Hong Kong. Data collection was carried out through aninterview and Focus Group Discussions (FGD). Selection of informants using Snowball samplingtechniques. The data validity test was carried out by triangulation with the Consulate General of theRepublic of Indonesia (KJRI) in Hong Kong and the National Agency for the Placement and Protection ofIndonesian Workers (BNP2TKI). The results showed that: 1) PMI smartphone communication based inHong Kong was mainly carried out using WhatsApp and video calls. The reason for using WhatsApp isthat it's cheap and has a variety of features. Besides WhatsApp, PMI is also using Facebook andInstagram as a form of socialization. 2) The communication network of the PMI Group in Hong Kong isdivided into a family network, a network of friends, a network of government representatives, and anetwork of other groups. In the group communication network pattern, PMI has been successfullyidentified as a star or opinion leader, liason, bridge and isolation. Keywords :  Group Communication, Indonesian Migrant Workers, Hong Kong